PENILAIAN SAHAM PT. SARA LEE INDONESIA TBK. DALAM RANGKA RENCANA PENAWARAN TENDER OLEH UNILEVER HOLDING B.V. - , Yufrizal Yusuf, Ir. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study aims to estimate the value ofthe shares of PT. Sara Lee Body Care Indonesia Tbk in the framework of the tender offer by Unilever Indonesia Holding BV The analytical tool used in this study were Approaches Revenue (Income Approach) method of Future Economic Income Discount (DCF) by applying the model ofthe equity cash flow (Free Cash Flow to Equity) and the Market Data Approach (Relative Valuatio) using a multiple of the company-comparable to PT. Sara Lee Body Care Indonesia Tbk. Multiple used are: Price Earning Ratio(PER), Price to Book Value (PBV) and Price to Sales Ratio (P /S) Data use dinthis study is the annual report and companyâs financial report which have been audited by Public Accountant period 2006-2010 (which ends on 30 June), published by the company. Besides, it also uses companyâs data presentation to the public and investors that are available on the Company website. Data was also obtained from Thomson Reuters customer service as well as PT. Sara Lee Body Care Indonesia Tbk. By using both approaches lead to the conclusion of the fairmarket value of shares. Sara Lee Body Care Indonesia Tbk in the framework ofthe tender offer as of June 30, 2010 at Rp454.383,-(four hundred and fifty four thousand three hundred and eighty-three rupiahs). This value indicates that the stock price of the tender offer PT. Sara Lee Body Care Indonesia Tbk has been undervalued.